2013
DOI: 10.1016/j.carbon.2013.07.057
|View full text |Cite
|
Sign up to set email alerts
|

Core-leaf onion-like carbon/MnO2 hybrid nano-urchins for rechargeable lithium-ion batteries

Abstract: A hybrid nano-urchin structure consisting of spherical onion-like carbon and MnO2 nanosheets is synthesized by a facile and environmentally-friendly hydrothermal method. Lithium-ion batteries incorporating the hybrid nano-urchin anode exhibit reversible lithium storage with superior specific capacity, enhanced rate capability, stable cycling performance, and nearly 100% Coulombic efficiency. These results demonstrate the effectiveness of designing hybrid nano-architectures with uniform and isotropic structure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 46 publications
2
53
0
1
Order By: Relevance
“…The plateau at 0.75 V disappeared and the one at 0.48 V was shortened in subsequent discharge cycles, which confirm the formation of a metallic manganese and lithium oxide matrix. [22,[35][36][37] This discharging/charging behavior was consistent with each other, as shown in Figure 7, and the MnO 2 /rGO composite was superior to that of the pure MnO 2 and MnO 2 / graphene electrodes. The specific capacity of pristine MnO 2 was 1573 mA h g À1 in the first discharge cycle, which was substantially larger than the theoretical value (1230 mA h g…”
Section: Resultssupporting
confidence: 86%
“…The plateau at 0.75 V disappeared and the one at 0.48 V was shortened in subsequent discharge cycles, which confirm the formation of a metallic manganese and lithium oxide matrix. [22,[35][36][37] This discharging/charging behavior was consistent with each other, as shown in Figure 7, and the MnO 2 /rGO composite was superior to that of the pure MnO 2 and MnO 2 / graphene electrodes. The specific capacity of pristine MnO 2 was 1573 mA h g À1 in the first discharge cycle, which was substantially larger than the theoretical value (1230 mA h g…”
Section: Resultssupporting
confidence: 86%
“…Specifically, the porous and flower-like structure could provide a large and accessible surface area to greatly enhance surface ion adsorption, improve the accessibility of cations and shorten the ion diffusion path. 2,17 The smaller and uniformly sized nanoparticles could also facilitate fast charge transfer on the surface or sub-surface of the active material; for example, Duay et al 12 found that the specific capacitance was much higher for small MnO 2 nanofibrils (5-10 nm) than for large MnO 2 nanowires (4.5 μm). In addition, although MnO x could be gradually oxidized to a higher valent state during the charge/discharge process, the structural features associated with the as-prepared MnO x , such as ionic (e.g., vacancies and misplaced ions) and electronic (electrons and holes) defects and mismatches at different phases, could still be preserved because of the slow and mild nature of the process.…”
Section: Resultsmentioning
confidence: 99%
“…13 However, despite a few examples of MnO x reported recently, 14 most previous studies simply denoted the synthesized Mn oxides as MnO 2 with few or no structural investigations. [15][16][17] The integration of MnO x into supercapacitor electrodes with binders is also challenging because of the non-uniform particle size, poor electrical conductivity and structural instability of MnO x . In addition, MnO x was mainly synthesized by methods involving hazardous chemicals, strong acids and high-temperature thermal annealing, with the controllability, scalability and reliability of these methods remaining unclear.…”
Section: Introductionmentioning
confidence: 99%
“…An equivalent circuit model was used to simulate the electrical components (inset of Supplementary Figure S11), where R s represents the current collector and electrolyte resistance; R f and CPE 1 are the SEI layer resistance and the constant-phase element (CPE), respectively; R ct and CPE 2 are the charge transfer resistance and double-layer capacitor, respectively; and W is the Warburg impedance related to lithium diffusion. 37 The fitting results were summarized in Supplementary Table S2, which clearly shows that the charge transfer resistance of the MoS 2 /VGNS electrode was significantly increased from 28.73 to 228.27 Ω when the amount of Mo salt precursor was increased from 3 to 22 mg. The highest charge transfer resistance was observed on the MoS 2 /CB control sample, indicating the poor electrical conductivity of the system.…”
Section: Mos 2 /Vgns Libs and Her Y Wang Et Almentioning
confidence: 99%